The theoretical and methodologial aspects os social representation about to teach: building teaching identities (Research, Society and Development, 2019)
The present article is a result of the research Teaching in the Degree: Social Representations in Construction developed at the Federal University of Rio Grande do Norte - UFRN that aimed to access the social representations of undergraduate students about teaching, and to find what relationships they did with their identity teacher construction. Here we make a cut of the material collected from semistructured interviews (SZYMANSKI, 2002) in order to better discuss the theoretical and methodological aspects of the teacher identities forged by the undergraduate students with the use of their representations about teaching. This work is in the field of studies on social representations (MOSCOVICI, 2012) and professional identity (DUBAR, 1997) and discusses how the references used by graduates to become teachers are objects created from what was experienced by the individual in basic education also the new concepts offered by graduation.